Zum Wesen der fremdsprachlichen Einkodierungsprozesse. On the nature of the foreign-language encoding-processes. - Szczodrowski, Marian (Glottodidactica, 2016)
The following article considers the concept of the trichotomous arrangement of codeprocesses involved in acquiring foreign languages. It particularly focuses on the site, course, and results of processes whereby foreign-language structures are encoded. The processes of encoding known foreign-language structures take place: first, during the completion of consolidating exercises that aim at attaining appropriate proficiency; second, in the course of decoding and coding foreign-language information; and third, in the course of ego-centered communicative processes, in which the language user fulfills the function both of sender and of receiver.